Stress relaxation in polymeric microlattice materials. (15th September 2017) - Krödel, Sebastian; Li, Lichen; Constantinescu, Andrei; Daraio, Chiara
Abstract: Breakthroughs in fabrication techniques enabled the creation of microlattice materials, which are assembled from truss-like elements on the micro-scale. The mechanical properties of these materials can be controlled varying the geometry of their microstructure. Here, we study the effect of topology and effective density on the visco-elastic properties of microlattices fabricated by direct laser writing. We perform micro scale relaxation experiments using capacitive force sensing in compression. The experimental results are analyzed using a generalized Maxwell model and the viscoelastic properties are studied in terms of density scaling laws. We develop a finite element model that allows extracting the bulk polymer viscoelastic properties. The experimental results show that the stiffness of lattice materials can be adjusted independently from the loss factor in a wide range of frequencies. We find that the loss factor dramatically increases with applied strain due to the onset of nonlinear dissipation mechanism such as buckling and plasticity. We show that at effective densities around 50% the energy dissipation per cycle in a microlattice outperforms the dissipation in the bulk, giving rise to a "less is more" effect. The present research defines a first step in the application of microlattice materials in vibration absorption. Graphical abstract: Highlights: The stress relaxation in polymeric microlattices was studied using microscale compression experiments. Microlattice viscoelastic properties can be tuned independently from their static performance. We predict that microlattices outperform bulk materials in their damping capabilities, leading to a "less is more" effect.